Subcutaneous administration of tocilizumab is effective in myointimal hyperplasia remodelling in refractory Takayasu arteritis - A. Lo Gullo; G. Mandraffino; C.O. Aragona; A. Molica Colella; A. Saitta; E. Imbalzano (PAGEPress Publications, 2017)
Takayasu arteritis (TA) is a chronic inflammatory disease of unknown origin that involves large and mediumsized arteries, primarily the aorta and its major branches. TA is a therapeutic challenge because corticosteroids and conventional immunosuppressive agents are not always effective or safe. Interleukin 6 (IL-6) has emerged as a key cytokine in the pathogenesis of TA and its serum levels have been shown to well correlate with disease activity. We report a 19 years old female patient with TA refractory to conventional immunosuppressive agents, successfully treated with subcutaneous tocilizumab, a humanized monoclonal antibody against IL-6 receptor, in which ultrasonography (US) was used as imaging tool to follow up the patient. Currently, clinical indices of disease activity, inflammatory markers, carotid intima media thickness (cIMT) as well as carotid pulse wave velocity (cPWV) normalised, while the prednisone dosage has been tapered. Tocilizumab appears to be a good option in refractory TA, with a remarkable steroid-sparing effect. In addition, it seems to have a favourable effect on endothelial function, as it improved cIMT and PWV.